Caracterização do desenvolvimento das habilidades motoras orais de crianças de 0 a 12 meses de idade nascidas pré-termo - Yamamoto, Raquel Coube de Carvalho (2017)
Objective: To characterize the feeding performance of prematurely born children in the first year of their lives, analyzing the stages of development of their oral motor skills in feeding with different food consistencies as well as different utensils. Methodology: Quantitative, descriptive and longitudinal study. The sample included 52 preterm newborns, who were assessed in the introduction of the oral route, and with four, six, nine and twelve months of corrected gestational age. The Premature Readiness Assessment Instrument was utilized for the beginning of the oral feeding, so as the Oral Feeding Skill Assessment and the Schedule for Oral Motor Assessment – SOMA. Results: At birth, the preterm newborns present an average gestational age of 32,7 (±1,9) weeks and weight of 1702 (±489,7) grams. In the feeding introduction through oral route, the corrected gestational age presented an average of 34,8 (±1,0) weeks and weight of 1830 (±337,6) grams. A significant statistical association (p<0,05) was observed within the result of the assessment SOMA in the baby bottle with readiness to start feeding. With four months, the presence of oral leaking occurred in 94,2% of the samples, and 84,6%.of the infants presented an oral motor dysfunction, reducing this proportion to 38,5% at six months of age. At six months, in the semisolid category, significant statistical association was found in the stratum of gestational age in the item chewing, beginning when the food is introduced into the oral cavity with 35% of the late premature infant presenting oral motor dysfunction; and in the SOMA results (p<0,05) showing that 97% of the extreme premature presented normal oral motor function. As to the utilization of glass with liquid, loss of extra oral liquid was observed in 82,7% of the sample, and tongue pulling out the liquid, in 71,2%. At the age of nine months, from the sixteen premature infant able to start feeding in the oral release, 43,7% presented oral motor dysfunction in the offering of the glass with liquid (p<0,05). In the assessment of feeding with cookies, 65,4% did not present closed lips during chewing, and 50% put the whole biscuit in the mouth. At twelve months, in the category solid, the preterm newborn that presented oral motor dysfunction had a gestational age below 34 weeks (p<0,05). In 61,5% of the children, loss of liquid during the use of glass was observed, and 65,4% of them did not present their lips closed while chewing the cookie. The presence of the jaw rotation movement was observed in 76,9% of the infants, demonstrating significant statistical association (p<0,05). Conclusion: Prematurity might be determinant in the arising of oral inadequacies on the feeding stages. At four months, the preterm newborn still does not present the oral motor skill needed for the introduction of complementary feeding. The difference of gestational age showed that it can interfere with the oral motor skill of the introduction of the solid consistency in the premature extreme to moderate at 12 months of corrected gestational age.